PUBLIC RELATIONS STRATEGY OF RSU ANANDA PURWOKERTO IN FACING CRISIS - Sintya Diar Nugrahaningsih; Mite Setiansah; Adhi Iman Sulaiman; Wisnu Widjanarko; Shinta Prastyanti (Sean Institute, 2023)
The termination of the cooperation relationship with BPJS Health has caused a crisis condition in the form of a decrease in the number of patients at Ananda Hospital Purwokerto. For this reason, the public relations strategy is very important to overcome this problem. This study uses a type of qualitative research with a constructivist paradigm. The purpose of this study is to find out how the Public Relations strategy is in dealing with crisis conditions in the form of a decrease in the number of patients due to the termination of cooperation with BPJS Kesehatan. The method is descriptive, while the technique for selecting informants is carried out using a purposive sampling technique, namely by determining which informants are considered knowledgeable about the problem being studied. Through in-depth interviews with informants, it is known that Public Relations formulates strategies in the form of an internal and external program redesign. Internally, Ananda Hospital is trying to research and redesign the budget based on a priority scale. In addition, a strategy with management reshuffle was also carried out. Innovation is also offered through excellent service for several services Furthermore, public relations plays a role in formulating a strategy so that patient referrals are prioritized to government hospitals in the hope that patients can return for treatment to Ananda Hospital. Besides that, the physical appearance of Ananda General Hospital is also polished to provide a more comfortable and impressive appearance for patients and visitors. Public Relations also disseminates daily content promos according to the most updated events. For the external strategy, public relations optimizes commercial services, such as home care and medical check-ups. In addition, public relations together with the director routinely make external visits and join communities that have the potential to bring benefits. All of these internal and external services are disseminated through social media to optimize the expected goals.